The Influence of Emotional Intelligence on the Academic Achievement of Class IX Male Students at MTs Ummul Quro Al-Islami Bogor - Pirman; Nur Ramadhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Intelligence and emotions play an important role in the learning process for students. Without participating in the emotional appreciation of the topics discussed in class, IQ cannot function properly. However, IQ and EQ are usually the key to a student's success in school. Researchers want to conduct additional research on